City Services by Design: Policy Feedback, Social Construction, and Inequality. (March 2019) - Grogan-Myers, Patrick; Hatch, Megan E.
This article reviews Jessica Trounstine's book Segregation by Design: Local Politics and Inequality in American Cities, situating it within the literature on local government policies, segregation, and inequality. In doing so, we demonstrate social construction and policy feedback reinforce the relationship Trounstine identifies between property owners' desire to protect their property values, local government policies, segregation, unequal services, and political polarization.